Finite-/Fixed-Time Synchronization of Memristor Chaotic Systems and Image Encryption Application - Wang, Leimin; Jiang, Shan; Ge, Ming-Feng; Hu, Cheng; Hu, Junhao (IEEE transactions on circuits and systems. I, Regular papers, 2021)
In this paper, a unified framework is proposed to address the synchronization problem of memristor chaotic systems (MCSs) via the sliding-mode control method. By employing the presented unified framework, the finite-time and fixed-time synchronization of MCSs can be realized simultaneously. On the one hand, based on the Lyapunov stability and sliding-mode control theories, the finite-/fixed-time synchronization results are obtained. It is proved that the trajectories of error states come near and get to the designed sliding-mode surface, stay on it accordingly and approach the origin in a finite/fixed time. On the other hand, we develop an image encryption algorithm as well as its implementation process to show the application of the synchronization. Finally, the theoretical results and the corresponding image encryption application are carried out by numerical simulations and statistical performances.